Acquisition and variation of the affricate palatal phoneme in Panama City: a phonetic-acoustic study in fifth-grade children - Macías, Heidy (Espergesia, 2025)
This study compiled, organized, and critically analyzed a body of research on the behavior of the tense palatal affricate /t͡ʃ/ in Spanish, especially in the Panamanian variety of Spanish. It was found that the tense palatal affricate /t͡ʃ/ exhibits interesting variations in terms of phonetic context, age group, and geographic distribution as the most notable aspects. In the Panamanian context, the first studies revealed marked differences, ranging from having recorded the affricate /t͡ʃ/ as the only allophone or the sound being clearly evolving into a fricative /ʃ/ to recognizing a process of articulatory lenition. Furthermore, research was conducted on the fricativization of this sound and its realization in American countries, including Panama and parts of Spain. Other concurring conclusions argued for the articulation of both allophones, the affricate /t͡ʃ/ and the fricative /ʃ/, in many Spanish-speaking regions. For example, a study conducted in Puerto Rico documented six different types of realization of this phoneme. The various investigations thus indicated that in the realization of this sound there is a phonetic alternation or variation that has been of interest to many scholars for some time. Therefore, interest was sparked in understanding the most relevant bibliography on this articulation when it comes to configuring its variation according to the variables that condition it.